Global Analysis of the Genetic Variations in miRNA-Targeted Sites and Their Correlations With Agronomic Traits in Rapeseed - Xu, Pengfei; Zhu, Yantao; Zhang, Yanfeng; Jiang, Jianxia; Yang, Liyong; Mu, Jianxin; Yu, Xiang; He, Yuke (Frontiers in Genetics, 2021)
MicroRNAs (miRNAs) and their target genes play vital roles in crops. However, the genetic variations in miRNA-targeted sites that affect miRNA cleavage efficiency and their correlations with agronomic traits in crops remain unexplored. On the basis of a genome-wide DNA re-sequencing of 210 elite rapeseed (Brassica napus) accessions, we identified the single nucleotide polymorphisms (SNPs) and insertions/deletions (INDELs) in miRNA-targeted sites complementary to miRNAs. Variant calling revealed 7.14 million SNPs and 2.89 million INDELs throughout the genomes of 210 rapeseed accessions. Furthermore, we detected 330 SNPs and 79 INDELs in 357 miRNA target sites, of which 33.50% were rare variants. We also analyzed the correlation between the genetic variations in miRNA target sites and 12 rapeseed agronomic traits. Eleven SNPs in miRNA target sites were significantly correlated with phenotypes in 3 consecutive years. More specifically, three SNPs within the miRNA-binding regions of BnSPL9-3, BnSPL13-2, and BnCUC1-2 were highly related to the branch angle, seed weight, and silique number, respectively. The results of this study provide researchers and breeders with a global overview of the genetic variations in miRNA-targeted sites in rapeseed. Moreover, the potential effects of these genetic variations on elite agronomic traits were elucidated.